Implementing Proactive Classroom Management in an Effective Classroom Management Approach for Students in Schools - Nugroho, Hanan Rasyid Alfianto; Nafiah, Kamilatun; Hutagaol, Rahel Tio Srilinsky; Sirait, Caroline Christine (Jurnal Inovasi Pembelajaran Karakter, 2025)
Effective classroom management is a key factor in creating a conducive learning environment for students. The application of proactive classroom management can serve as an effective approach to preventing behavioral issues and enhancing student engagement in the learning process. Proactive classroom management involves careful planning, the creation of a supportive learning environment, and the development of positive relationships between teachers and students. The primary focus is not only on disciplinary actions but also on prevention strategies, fostering good habits, and managing constructive social interactions. This approach includes techniques such as establishing classroom routines, providing constructive feedback, and implementing differentiated instruction to meet the diverse needs of students. By applying proactive classroom management, it is hoped that a harmonious, safe, and enjoyable learning atmosphere can be created, encouraging students to develop optimally.